A conceptual approach to vocational training in fragile contexts - bridging education and economic development: Inspired by a scoping mission to Somalia - Stefan Wolf; Nicole Rudner (Austrian Foundation for Development Research (ÖFSE), 2021)
The aim of the scientific concept study was to determine whether vocational education and training can contribute to supporting social and economic rehabilitation in fragile, particularly dysfunctional, contexts. And if so, by what means could this be achieved in a favourable way? Our theoretical and methodological approach follows an interdisciplinary perspective that combines both comparative vocational education research and international development research, with particular emphasis on fragility and conflict. The selected design for the case study on Somalia follows a mixed-method approach of combining desk research, field studies with interviews and observations, validation workshops of the different parts of the findings. An extended, multi-level qualitative study was conducted. We have developed a conceptual proposal on how vocational training and economic development can be linked in the context of fragility and dysfunctional statehood in Somalia and implemented for the positive development of the country. We have been able make a concise contribution to the nexus between education in emergencies and the specific role of vocational education with its limits and extensions with conflicts and fragility. We propose a new concept to cope with the situation of education and economic development under conditions of state fragility, crisis and conflict. We have named it TVET+ Service Hub, which combines the still separate fields of TVET with economic development and societal wellbeing in one institution. While for the time being our propositions refers to one specific institution to be set up in Somalia with funds from an international donor organisation, its future progress will show the possibilities of generalising this approach.
Keywords: 330; TVET and Fragility; Education in Emergency; Conflict and Crisis Prevention; Economic Development and TVET; Somalia